Cardiac rhabdomyoma in a slaughtered heifer - Ramírez-Romero, Rafael; Ramírez-Hernández, Cecilia (Brazilian Journal of Veterinary Pathology, 2015)
During routine inspection of a slaughtered heifer from a feedlot, the veterinarian in charge condemned the heart due to a lesion on the endocardium. Histopathology and immunohistochemistry showed that the lesion was composed by cardiac tissues at different degree of differentiation, disordered and out of proportion. The most conspicuous was a dispersed population of large, vacuolated and PAS positive cells, enmeshed in excessive fibrous connective tissue. These cells, identified as spider cells, resulted markedly positive for desmin, and negative for vimentin, smooth muscle α-actin and myogenin factor 4. An extensive infiltration by fibro-fatty tissue was other abnormal component of the lesion. Furthermore, abnormal cardiomyoblasts forming tortuous bundles were also recognized. Nonetheless, these cells showed distinctive striations and even intercalated discs. Some of this abnormal cardiac myoblasts resulted markedly positive for desmin and isolated strands also were positive for smooth muscle α-actin, but negative for myogenin factor 4 and vimentin. Based on the pathognomonic spider cells and immunoreactivity, the lesion was classified as a cardiac rhabdomyoma. For some, the cardiac rhabdomyomas are not true neoplasms but congenital hamartomas in heart. However, principal component in cardiac hamartomas in animals is an abnormal vascular pattern completely different from the lesion herein presented. Based on the diverse tissue components, their immature and distorted image and, positive results for immunomarkers of early myoblast differentiation as well as terminal cardiomyocyte characteristics, dysplasia must be considered as the common denominator in development of cardiac rhabdomyomas with tissue heterogeneity.